Carbon films deposition by filtered cathodic vacuum arc technique - Tay, Beng Kang (2012)
Thin carbon films have been deposited by filtered cathode vacuum arc technique and a low bias voltage power supply. The substrate bias voltage ranged from -80 to -400V. It is important for thin films to have low internal stress and good adhesive properties for any applications. The results ascertain that stress levels were high at the bias voltage between -100 and -200V. By analysing the relationship between the compressive stress and the negative bias voltage applied on substrates, certain trends can be observed. Stress levels fluctuate greatly between -100V and -170V and the peak stress level would occur in this range. Delamination is likely to take place on films will high level of stress.